Mentorship and induction practices with novice foundation phase teachers: an exploratory case study with six primary schools novice teachers and leadership in Johannesburg, South Africa. - Dyosini, Thokozane Princess (My University, 2022)
The purpose of this study was to explore and develop an understanding of mentorship and induction as evolving forms of job-embedded continuous professional development for novice teachers in the foundation phase. To develop this understanding, this research posed the question: How can having access to induction and mentorship serve as professional support for novice teachers in the FP? Mentorship entails the provision of professional and personal guidance by a mentor to an assigned mentee. Induction involves providing focused career assistance in a particular community of practice, inducting the novice into the ethos and culture of the institution. This research study used a qualitative research approach and data was generated using semi-structured interviews with ten research participants. The objective of this research was to explore whether novice teachers are currently being inducted and mentored from the perspective of ten participants – mainly, six novice teachers, two heads of department and two primary school principals. the participants shared their perspectives, experiences, perceived expectations and challenges of either having received mentorship or the lack thereof during their first three years of teaching. All ten participants are in-service teachers working in the foundation phase at different inner-city schools in Johannesburg, South Africa. Novice teachers in the foundation phase face an array of issues and challenges in their early years of teaching as professionals. The participants were purposively selected. In addition, thematic content analysis was used to analyse the data attained. The positioning theory by Harré & Van Langenhove (1999) was used as the theoretical framework, as it foregrounded the theory of the participants having various positions and interpretations of their contexts through the use of social episodes. School leadership is expected to either facilitate or create opportunities for novice teachers to gain access to continuous professional development. Communities of practice by Wenger (2011) was used as the conceptual framework as a means to identify and explain the participants contexts. A case study of each participant group revealed their perspectives and communicated the nuances of providing professional development and the implications it would have on novice teachers. The findings revealed a strong sense of novice teachers needing continuous professional support on different levels. The participants shared that their mental health and professionalism challenges amongst other aspects that were greatly affected by the lack of professional development support. This research recommends the need for providing a consistent and structured policy for the implementation of induction, mentorship and coaching as components of professional development. In addition, it is advised that the mentors and mentees are paired, guided and evaluated during the entire process. This support-based approach needs to be holistic in order for it to be effective, including guidance in areas of professional (career, academia, skills and expertise) and personal (work/life balance, self-confidence, self-perception, wellness, mental health, and personal influences) development.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, 2022